"Biting Our tongues": Policy Legacies and Memories in the Making of the Syrian Refugee Response in Jordan. (23rd May 2020) - Lenner, Katharina
Abstract: This article analyses the significance of policy legacies and policy memories for refugee policy in conflict-neighbouring countries, where most of the world's displaced live. Drawing on insights from critical policy analysis, it views refugee policy as co-produced by national and international agencies on the basis of previous dynamics that are already the product of an intense history of interaction and translation. This approach is illustrated by analysing two different aspects of refugee policy in Jordan: the process of counting Syrians in the country and the partial integration of Syrians into the formal labour market. Both examples reveal an overarching legacy of accommodation that ties international and host government actors together. Despite sometimes differing over preferred outcomes, the main goals for the various actors involved have been to strike compromises, safeguard organisational interests, and create outward policy success. In order to meet these goals, the agencies involved have learned to tolerate unresolved ambiguities and disregard other inconvenient legacies and memories that would only complicate policy negotiations. Acknowledging this intertwinement of agencies, technologies, and rationales of government is essential for rethinking policy change and responsibility in contexts of mass displacement.